ANTIOXIDANT, ANTI-INFLAMMATORY AND ANTI-NOCICEPTIVE PROPERTIES OF HYDRO-METHANOL EXTRACT OF EREMOMASTAX SPECIOSA (HOCHST.) CUFOD LEAF - Onoja, Samuel O.; Eke, Chinemerem; Ejiofo, Emmanuel; Madubuike, Kelechi G.; Ezeja, Maxwell I.; Omeh, Yusuf N.; Anaga, Aruh O. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Eremomastax speciosa (Hochst.) Cufod is a perennial herb found in Africa along the rainforest zone and occurs as weed. It is cultivated in Cameroon and Akwa-Ibom in Nigeria due to its medicinal values. This study investigated the antioxidant, anti-inflammatory and antinociceptive properties of hydromethanol extract of Eremomastax speciosa (Hochst.) Cufod leaf in rat model. Materials and Methods: The plant material was extracted using cold maceration method in 80% hydromethanol. The acute oral toxicity test was performed using Up and Down method with limit dose of 2000 mg/kg. The in vitro antioxidant property was evaluated with 2,2-diphenyl-1-picrylhydrazyl and ferric reducing antioxidant power photometric assays. The anti-inflammatory potential was investigated in egg-albumin and carrageenan induced paw edema models while the antinociceptive activity was determined using acetic acid induced writhing reflex and tail immersion tests at the doses of 50, 100 and 200 mg/kg. The negative control group (group A) received distilled water (vehicle) at 5 ml/kg while acetyl salicylic acid (200 mg/kg) was used as the reference drug for the anti-inflammatory models and acetic acid induced writhing reflex model while pentazocine (5 mg/kg) was used as the reference drug for tail immersion test. Results: The LD50 of the extract was greater than 2000 mg/kg. The extract (25 to 400 μg/ml) demonstrated potent antioxidant activities in both the 2,2-diphenyl-1-picrylhydrazyl and ferric reducing antioxidant power assays. The E. speciosa extract caused significant (P < 0.05) anti-inflammatory and antinociceptive activities in the extract treated groups when compared to rats that received distilled water. The optimal activities of the extract were produced at the dose of 100 mg/kg. Conclusion: The study supports the folkloric use of Eremomastax speciosa leaf in the management of pain and inflammatory conditions in traditional medicine.